3x + 5 + x + 10 + 2y 4x + 2y + 15 |:2 2x + y + 7.5 2x + y + 7.5 is equivalent to the original.
It is the same. The equation "x + y" is the exact same as "x + y." There is no difference.
xy + x + y + 1 = (x + 1)(y + 1).
xz + x + yz + y = (x + y)(z + 1)
y + 12 = -3(x - 2) y + 12 = -3x + 6 y = -3x - 6 or y = -3(x + 2)
y += x means the value y+x is first calculated, and the resulting value is then assigned to y. It is equivalent to y = y+x
x + 2 = y x - y + y - x = 0, even though what is y equivalent. Are you sure, you are looking for something else?
It is equivalent to x + y + 4.
True
5(x + y)
y
There is no non-trivial equivalent.
3x + 5 + x + 10 + 2y 4x + 2y + 15 |:2 2x + y + 7.5 2x + y + 7.5 is equivalent to the original.
Oh, dude, you're hitting me with some math here. So, like, you've got 4 x's and 3 y's, right? So, you can simplify that expression as 4x + 3y. It's like organizing a messy room, but with letters and numbers.
(x + y)(x + y)(x + y)
The answer to Y x plus 5 Y 6 is Y(x+5Y5).One possible solution to y x plus 5 y 6 is Y(x+5Y5).
c